Advantages of electronic nursing documentation in nursing practice - Malliarou, Maria; Damigou, D.; Sarafis, Pavlos (My University, 2009)
To identify the role and usefulness of electronic nursing documentation as long as its benefits on quality of nursing practice.
Keywords: Εlectronic nursing documentation; Νursing practice